Taxonomy of the ant genus Pheidole Westwood (Hymenoptera: Formicidae) in the Afrotropical zoogeographic region: definition of species groups and systematic revision of the Pheidole pulchella group - Fischer, Georg.; Garcia, Francisco Hita; Peters, Marcell K. (Zootaxa, 2012)
This paper is a starting point towards a much needed comprehensive taxonomic treatment of the genus Pheidole in theAfrotropical region. Despite its hyperdiversity, the taxonomy of this globally distributed ant genus is limited to importantrevisions for the New World and several Asian faunas. However, Pheidole of the Afrotropical zoogeographic region hasnever been revised. The most recent Afrotropical Pheidole species descriptions are fifty years old and many are consider-ably older. Identification keys are not available and many species descriptions are of limited diagnostic value. This callsfor a series of taxonomic revisions in order to resolve the complicated taxonomic situation for the complete AfrotropicalPheidole fauna. In this paper the following preliminary morphological species groups for the Afrotropical region are de-fined: P. aurivillii group, P. excellens group, P. megacephala group, P. nigeriensis group, and P. speculifera group. We also establish and revise the P. pulchella group, which currently contains eleven species, of which seven are new. The four spe-cies described prior to this study are: P. pulchella Santschi, P. dea Santschi, P. nimba Bernard, and P. batrachorum Wheelerstat. rev., which is removed from synonymy under P. dea and regains species status. The following new synonymy isproposed (senior synonym listed first): P. pulchella Santschi = P. pulchella achantella Santschi. The following seven spe-cies are described as new: P. christinae sp. n., P. darwini, sp. n., P. glabrella sp. n., P. heliosa sp. n., P. rebeccae sp. n., P. semidea sp. n. and P. setosa, sp. n. An illustrated key combining the minor and major worker subcastes is presented.